Comprehension of an Over-the-Counter Drug Facts Label Prototype for a Mifepristone and Misoprostol Medication Abortion Product. Issue 6 (2nd June 2022) - Biggs, M. Antonia; Ehrenreich, Katherine; Morris, Natalie; Blanchard, Kelly; Bustamante, Claudie Kiti; Choimorrow, Sung Yeon; Hauser, Debra; Hernandez, Yamani; Kapp, Nathalie; Kromenaker, Tammi; Moayedi, Ghazaleh; Perritt, Jamila B.; et al.
Abstract : High levels of comprehension suggest that people can understand most key concepts of a nonprescription medication abortion drug facts label prototype without clinical supervision. Abstract : OBJECTIVE: To develop a drug facts label prototype for a combination mifepristone and misoprostol product and to conduct a label-comprehension study to assess understanding of key label concepts. METHODS: We followed U.S. Food and Drug Administration guidance, engaged a multidisciplinary group of experts, and conducted cognitive interviews to develop a drug facts label prototype for medication abortion. To assess label comprehension, we developed 11 primary and 13 secondary communication objectives related to indications for use, eligibility, dosing regimen, contraindications, warning signs, side effects, and recognizing the risk of treatment failure, with corresponding target performance thresholds (80–90% accuracy). We conducted individual structured video interviews with people with a uterus aged 12–49 years, recruited through social media. Participants reviewed the drug facts label and responded to questions to assess their understanding of each communication objective. After transcribing and coding interviews, we estimated the proportion of correct responses and exact binomial 95% CIs by age and literacy group. RESULTS: We interviewed 851 people (of 1, 507 people scheduled); responses from 844 were eligible for analysis, and 35.7% (n=301) of participants were aged 12–17 years. The overall sample met performance criteria for 10 of the 11 primary communication objectives (93–99% correct) related to indications for use, eligibility for use, the dosing regimen, and contraindications; young people met nine and people with limited literacy met eight of the 11 performance criteria. Only 79% (95% CI 0.76–0.82) of the overall sample understood to contact a health care professional if little or no bleeding occurred soon after taking misoprostol, not meeting the prespecified threshold of 85.0%. CONCLUSION: Overall, high levels of comprehension suggest that people can understand most key drug facts label concepts for a medication abortion product without clinical supervision and recommend minor modifications.